The Role of Motivation, Attitude, Anxiety and Instrumental Orientation in Influencing Learner's Performance in English as a Second Language in OUM - Latifah Abdol Latif; Mansor Fadzil; Ramli Bahroom; Wardah Mohamad; Ng, Man San (2011)
The objective of this research is to determine the relationship between the various socio-psychological variables like attitude, motivation, anxiety and instrumental orientation on performance in English as a second language. An impact study of each of the variables on learners' performance was also carried out in order to elucidate the variable that is most significant. A survey methodology was used, in which 757 out of the 2016 questionnaires were used. The results indicate that all the four variables were significantly correlated with learners' performance in the English course conducted at Open University Malaysia (OUM). The regression analysis showed that all the variables except for personal motivation exert significant impacts on performance with anxiety having a negative impact while attitude and instrumental orientation having positive impacts. Several implications were discussed and some recommendations were put forth, taking into consideration the open and distance learning environment at OUM. (Abstract from authors)